2012
DOI: 10.1111/j.1471-0528.2012.03490.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous preterm delivery in women with threatened preterm labour: a prospective cohort study of multiple proteins in maternal serum

Abstract: Sir, I was interested to read the paper by Tsiartas and colleagues 1 published in the June 2012 issue of BJOG. The authors reported the prediction of preterm labour by building a model using a cohort data set. As the authors point out in their conclusion, such a model needs to be tested in a new cohort in order to confirm its predictive ability. Why did the authors not divide their cohort into two and develop the model on one half and test it on the other? Or use other methods such as bootstrapping to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 3 publications
3
28
1
Order By: Relevance
“…In addition, the current study demonstrates that combining multiple biomarkers, especially with clinical data, can improve the accuracy of risk prediction for preterm birth, and these combinations are more accurate than using each of these biomarkers alone. These findings are in agreement with the results of previous studies in the setting of preterm labor and intact membranes . These observations may be attributed to the fact that preterm parturition is associated with the upregulation of various chemokines and MMPs, as well as traditional proinflammatory cytokines; thus, the evaluation of multiple biomarkers in AF can more precisely represent this inflammatory process in vivo , as well as the fact that spontaneous preterm birth has a multifactorial etiology …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the current study demonstrates that combining multiple biomarkers, especially with clinical data, can improve the accuracy of risk prediction for preterm birth, and these combinations are more accurate than using each of these biomarkers alone. These findings are in agreement with the results of previous studies in the setting of preterm labor and intact membranes . These observations may be attributed to the fact that preterm parturition is associated with the upregulation of various chemokines and MMPs, as well as traditional proinflammatory cytokines; thus, the evaluation of multiple biomarkers in AF can more precisely represent this inflammatory process in vivo , as well as the fact that spontaneous preterm birth has a multifactorial etiology …”
Section: Discussionsupporting
confidence: 91%
“…Specifically, in terms of reflecting intra‐amniotic infection and/or inflammation, interleukin (IL)‐6 and matrix metalloproteinase (MMP)‐8 in amniotic fluid (AF) have been suggested as surrogate biomarkers for the prediction of preterm birth in women with cervical insufficiency . Importantly, a recent study aimed at predicting preterm birth in women with preterm labor and intact membranes demonstrated that the combined use of multiple biomarkers in AF, cervical fluid and maternal blood, and clinical factors substantially improved diagnostic efficiency and had better predictive accuracy than any of the biomarkers alone . This observation is not surprising given that the evaluation of multiple biomarkers representing several distinct biological pathways may provide additional information about the biological status of the disease, as well as additional prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several recent studies have focused on predictors of these outcomes by utilizing noninvasively collected samples (i.e., cervicovaginal fluid [CVF] or maternal serum). [9][10][11][12][13][14] However, most studies have not yet found reliable biomarkers in either the CVF or maternal blood compartment alone, which have high sensitivity and specificity comparable with those of AF sampling-based tests. Moreover, to date, there is little information regarding whether cytokine/ chemokine expression in both the CVF and maternal blood compartment is influenced by immune-inflammatory responses elicited by microbes in the AF compartment.…”
mentioning
confidence: 99%
“…These five analytes were selected on the basis of previous findings that their levels were altered in the AF, serum, and CVF in women with PTL in relation to MIAC, IAI, and imminent SPTD. [11][12][13][14]17 We aimed to assess the correlations among multiple cytokine/chemokine levels in AF, CVF, and maternal plasma in women with PTL, and to develop models using these protein levels in CVF and plasma along with widely used noninvasive parameters that have better accuracy for predicting IAI and imminent SPTD ( 48 hours).…”
mentioning
confidence: 99%
“…It can lead to preterm delivery, which has high neonatal morbidity and mortality . The resulting preterm delivery can also be a substantial cause of emotional and financial stress to parents and society …”
Section: Introductionmentioning
confidence: 99%